Memorandum on home treatment service
1940-12-17 1940 1940s 4 pages Revise 1, 17.12.40. MEDICAL PRACTITIONERS' UNION. Memorandum on Home Treatment Service. INTRODUCTION. It appears to the Union that we cannot expect our old and accustomed methods of panel and private practice to continue indefinitely, and that some form of State Service must inevitably take their place. There are many reasons for this view. Some of these arise out of war conditions. Other reasons are implicit in the tendencies of municipal medicine. Every year the lure of free treatment attracts more and more of our patients to Municipal Clinics, while much work that we could very well do, e.g., anti-diphtheria inoculations, is handed over to salaried officials. Equally significant, and not less dangerous to our future, is the ever increasing state employment of Health Visitors and Midwives for work which was previously done by general practitioners. It is the avowed policy of many influential Health Officers to extend such measures until there is no place left for the independent general practitioner, and we have either to deal with this situation before it is too late by presenting a well thought out alternative or to reconcile ourselves to slow extinction, preceded by a period of dependence on the few private fees which we can manage to pick up. There are those who realise these threats, but think that some sort of extension of the contributory scheme would be a sufficient reply, but it seems evident to the Union that we cannot fight municipal free treatment except by offering better treatment which must be equally free to the patient. Nor should our members forget that the extension of the contributory panel system to dependants presents administrative difficulties which the best authorities have always regarded as insuperable. No one has been able to suggest any method of collecting subscriptions from or on behalf of dependants which does not involve hardships to the individual, of a type which no political party can run the risk of approving. It is these various circumstances, as well as many others which we have not named, which have compelled the Union to attempt the elaboration of a system of State provided home treatment which will satisfy the public and the profession alike. We well know that no form of State treatment can perpetuate in full force the kindly human relationships between doctor and patient which exist to-day. We well know the multiplicity of forms and the ignorance of clinical work which is usually found under State management. We are not shutting our eyes to these things nor are we seeking to persuade the profession to accept a State Service because we have some political or theoretical bias in favour of such service. We do so because we feel obliged to propose some remedy for the state of affairs set out above and because it is our duty to do what we can to meet the growing revolt (of which we have ample documentary evidence) against the long hours and excessive charity imposed by the present system upon general practitioners, many of whom are already past middle age, but see no hope of escape from the burden of practice, except in a service which will provide for honourable retirement on an adequate pension. The Union has examined over 2,000 replies to the request for observations on its first draft. A number of these declared themselves unable to accept this or that proposal, and therefore stated that they were not in favour of our scheme. But the great majority of replies were favourable. We must, therefore, go forward with our task, as our correspondents plainly expect us to do. We have now prepared this second draft for further consideration. 1. AVAILABILITY OF SERVICE. The benefits of the Service will be available without charge to all residents in Great Britain, without any income limit. It is expected that a limited class (represented by those who now send their children to private schools) will, at first, refrain from using the State Medical Service, but will prefer to employ such independent practitioners as may have chosen to remain outside the State Service, where any such are available. 292/847/1/23